Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s41257-021-00045-6
|View full text |Cite
|
Sign up to set email alerts
|

Inheritors of the Yellow River: the relationship of heritage making practices to cultural self-confidence in China

Abstract: Through active involvement in UNESCO’s ICH (Intangible Cultural Heritage) programme, China has developed its own framework to support traditional making practices. To examine the ‘characteristics’ of heritage crafts preservation in China, we undertook empirical research in the Yellow River basin. Our research involved in-depth observations and key informant interviews with a range of highly accomplished craftspeople who have inherited their particular expertise from their family and have been officially design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Since 2016, the policy of cultural confidence has been frequently on the agenda of important political meetings in China, such as the 20th National Congress of the Communist Party of China (Xi 2022). Studies have shown that the state power's emphasis on cultural development in China in recent years has been a direct driver of the country's cultural and creative industries (Tsai et al 2022), and the development of such industries has seen a top-down pattern of development (Zhang et al 2021).…”
Section: Dunhuang As Presented By the Wechat Mini-programmementioning
confidence: 99%
“…Since 2016, the policy of cultural confidence has been frequently on the agenda of important political meetings in China, such as the 20th National Congress of the Communist Party of China (Xi 2022). Studies have shown that the state power's emphasis on cultural development in China in recent years has been a direct driver of the country's cultural and creative industries (Tsai et al 2022), and the development of such industries has seen a top-down pattern of development (Zhang et al 2021).…”
Section: Dunhuang As Presented By the Wechat Mini-programmementioning
confidence: 99%
“…Traditional Chinese medicine is the treasure of ancient Chinese science and the key to open the treasure house of Chinese civilization. TCM has a vast territory and distinctive cultural characteristics [2]. The TCM culture of various regions has been continuously developed and improved in the process of history, and gradually formed a regional TCM culture full of distinctive characteristics.…”
Section: Lack Of Tcm Culturementioning
confidence: 99%
“…Despite their importance, studies on heritage masters are limited. These studies include determining the inventory of heritage masters (Küçük, 2019), learning the problems experienced by heritage masters (Deniz and Çelik, 2020;Öksüz, 2019), explaining the construction of heritage elements (Akyol, 2017;Çiçekoğlu, 2014;Kardaş, 2018), determining the tools and motifs used (Er and Gürel, 2020), learning the motivation and skills of the masters (Zhang et al, 2021). These studies were carried out emphasizing one aspect of heritage masters.…”
Section: Introductionmentioning
confidence: 99%